High sensitivity organic inorganic hybrid X-ray detectors with direct transduction and broadband response - H. M. Thirimanne (Nature Portfolio, 2018)
X-ray detectors based on low-cost organic semiconductors have inherently low detector sensitivity due to poor X-ray to charge conversion and charge collection. Here, the authors demonstrate a flexible, high-sensitivity X-ray detector based on an organic bulk heterojunction-nanoparticle composite.